L10-FeNi films on Au-Cu-Ni buffer-layer: a high-throughput combinatorial study. Issue 1 (December 2018) - Giannopoulos, G.; Barucca, G.; Kaidatzis, A.; Psycharis, V.; Salikhov, R.; Farle, M.; Koutsouflakis, E.; Niarchos, D.; Mehta, A.; Scuderi, M.; Nicotra, G.; Spinella, C.; et al.
Abstract The fct L10 -FeNi alloy is a promising candidate for the development of high performance critical-elements-free magnetic materials. Among the different materials, the Au-Cu-Ni alloy has resulted very promising; however, a detailed investigation of the effect of the buffer-layer composition on the formation of the hard FeNi phase is still missing. To accelerate the search of the best Au-Cu-Ni composition, a combinatorial approach based on High-Throughput (HT) experimental methods has been exploited in this paper. HT magnetic characterization methods revealed the presence of a hard magnetic phase with an out-of-plane easy-axis, whose coercivity increases from 0.49 kOe up to 1.30 kOe as the Au content of the Cu-Au-Ni buffer-layer decreases. Similarly, the out-of-plane magneto-crystalline anisotropy energy density increases from 0.12 to 0.35 MJ/m3 . This anisotropy is attributed to the partial formation of the L10 FeNi phase induced by the buffer-layer. In the range of compositions we investigated, the buffer-layer structure does not change significantly and the modulation of the magnetic properties with the Au content in the combinatorial layer is mainly related to the different nature and extent of interlayer diffusion processes, which have a great impact on the formation and order degree of the L10 FeNi phase.